Interaction of synthesized nitrogen enriched graphene quantum dots with novel anti-Alzheimer's drugs: spectroscopic insights. Issue 6 (12th April 2020) - Sharma, Srishti; Singh, Namrata; Nepovimova, Eugenie; Korabecny, Jan; Kuca, Kamil; Satnami, Manmohan L.; Ghosh, Kallol K.
Abstract: Alzheimer's disease (AD) is considered as one of widespread dementia with no approved diagnosis, cure or prevention. Currently, only symptomatic relief can be provided upon administration of anti-AD drugs generally belonging to a category of anticholinesterases and antagonists of N-methyl-D-aspartate (NMDA) receptors. In present investigation, a sensing platform has been designed for studying recently developed anti-AD drugs viz., PC-25 (N-(2-{4-[(4-bromophenyl)methyl]piperazin-1-yl}ethyl)-7-methoxy-1, 2, 3, 4-tetrahydroacridin-9-amine trihydrochloride), PC-37 (7-methoxy-N-(2-{4-[(3-methylphenyl)methyl]piperazin-1-yl}ethyl)-1, 2, 3, 4-tetrahydroacridin-9-amine trihydrochloride) and PC-48 (N-(2-{4-[(3-bromophenyl) methyl]piperazin-1-yl}ethyl)-7-methoxy-1, 2, 3, 4-tetrahydroacridin-9-amine trihydrochloride) and two known standard tacrine (THA) and donepezil drugs for their estimation of in vitro potency towards AD using spectroscopic method. Anti-AD drugs have been accounted for individually with highly fluorescent nitrogen-doped graphene quantum dots (NGQDs). The designed anti-AD drugs exerted the efficacy related to cholinergic hypothesis of AD. While the enzyme action is sensed by interacted species of NGQDs and acetylcholine, the fluorescence of NGQDs is quenched by the hydrolyzing action of acetylcholinesterase (AChE) enzyme but the lost fluorescence is recovered upon addition of anti-AD drugs. These alterations in fluorescence of NGQDs are expected to have biological relevance akin to sensing. Moreover, these results advocate that out of all the drugs tested PC-37 displayed maximum inhibition efficiency. Our investigations suggest that synthesized drugs have the AD treating potential and can be entrusted in the near future for AD treatment. The validation parameters such as LOD, LOQ and recovery (%) were calculated in the range of 2.87 mM, 9.58 mM and 85–96%, respectively. Communicated by Ramaswamy H. Sarma Abstract : Interaction of synthesized nitrogen enriched graphene quantum dots with acetylcholine. Recovery of quenched fluorescence upon addition of anti-Alzheimer drugs in a concentration-based manner.